Pengaruh Akuntabilitas, Profesionalisme, dan Integritas Auditor terhadap Kualitas Auditor - Baginda Sultan Aritonang; Evi Ekawati; Cris Kuntadi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to determine the effect of Accountability, Professionalism, and Auditor Integrity on Auditor Quality. Previous research or relevant research serves to strengthen the theory and penomena of relationships or influences between variables. This article reviews the factors that affect Auditor quality, namely Auditor Accountability, Auditor Professionalism, and Auditor Integrity a study of tax accounting literature. The purpose of writing this article is to build a hypothesis of the influence between variables to be used in further research. The results of this literature review article are: 1) Auditor Accountability affects Auditor Quality 2) Auditor Professionalism, and 3) Auditor Integrity have an effect on Auditor quality; and have an effect on Audit Quality.